Design and assessment of a 3D printing vending machine. Issue 5 (17th August 2015) - Meisel, Nicholas A.; Williams, Christopher B.
Abstract : Purpose: – The purpose of this study/paper is to present the design and implementation of a novel vending machine concept based on desktop-scale extrusion additive manufacturing (AM). Due to cost, access to AM technologies at academic institutions tends to be limited to upper-level courses to support project-based coursework. However, with the decreasing cost of desktop-scale AM technology, there is potential to improve student access to such technologies and provide more opportunities for AM education. Design/methodology/approach: – The authors present the design and implementation of an AM "vending machine" that is powered by desktop-scale extrusion-based AM systems. This system intends to provide students broad, unrestricted access to entry-level AM tools and promote informal learning opportunities. Findings: – Student users of the AM vending machine are found to be primarily engineering majors at various levels in their studies. Manufactured parts are evenly split between functional and decorative parts, though 75 per cent of students are creating their own designs rather than simply printing found design files. Research limitations/implications: – Future work will focus on improving the system's ease-of-maintenance, lowering the barrier to entry with a simpler user interface and establishing a method for better recording part and user information. Practical implications: – The interface of the AM vending machine lowers the barrier of entry into engaging with AM and places this emerging technology in a familiar and "safe" context. It provides students at various levels and disciplines the opportunity to fabricate parts for classroom and personal projects. Social implications: – A "vending machine" system may have far-reaching implications for public access and use of AM. Such broad access has the potential to further educate and impassion the public about the potential of AM. Originality/value: – This work represents the creation and assessment of the world's first AM vending machine.